Challenges Encountered Towards The Enhancement and Optimal Learning of The Creative Arts Subject In South Africa - Sakhiseni Joseph Yende; Ndwamato George Mugovhani; Simphiwe Magagula (Institut Seni Indonesia Yogyakarta, 2023)
In recent years, there have been debates regarding the scope of Creative Arts subject in the existing curriculum known as the Curriculum and Assessment Policy Statement offered in the South African public schools. Crucial points in question include the fact that the curriculum does not fully equip learners with the requisite skills for their respective areas of interest; and that these public schools are finding it difficult to get suitable and fully equipped educators for all the art forms (dance, music, drama, and visual arts) located within this Creative Arts subject. Presently there still need to be more skilled educators for this subject. This article sets out to interrogate these and many other challenges encountered in teaching and learning this subject. The study adopted a qualitative research method to collect data, using techniques such as semi-structured, structured, and sometimes convergent interviews with the principals, teachers, and selected learners from the selected public schools. A substantial review of previous and recent scholarly writings on the subject was done to substantiate the findings. A phenomenological data analysis was adopted whereby the primary findings were presented in themes and supported by the quotes from the participants. The over-arching finding, and conclusion is that this Creative Arts subject requires some intervention strategies and revision by government and all relevant stakeholders.